Hubungan Sikap, Pola Asuh Keluarga, Peran Orang Tua, Peran Guru dan Ketersediaan Sarana Dengan Perilaku Hidup Bersih dan Sehat - Yenie Chrisnawati; Dyah Suryani (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2020)
Background: Clean and Healthy Living Behavior (CHLB) is a collection of behaviors carried out by a person on self-awareness, obtained from the results of learning, to make a person, family, group, or society independent of health and play an active role in realizing health. Various diseases often appear and attack in school-age children related to CHLB. The implementation of CHLB indicators in schools can be influenced by many factors, including student knowledge, attitude, teacher role, parent role, media exposure, availability of infrastructure facilities, and other factors. The purpose of this study is to find out the factors related to clean and healthy living behavior (CHLB) in students of SD N Baturan II Sub-District Gamping Sleman District. Methods: This study uses cross-sectional studies. The population of this study is graded V and VI students at SD N Baturan II. The sampling technique was conducted with total sampling (39 respondents). The research instrument is a questionnaire. Analyze data with univariate analysis and bivariate analysis using the Chi-square test. Result: The results of the bivariate analysis showed that there was no relationship between attitudes and students' CHLB p=0.151, there was a relationship between family parenting and students' CHLB p=0.001, there was a relationship between the role of parents and students' CHLB p=0.018, there was no relationship between the role of teachers and CHLB students p =0.250, and there is no relationship between the availability of facilities and student CHLB p =0.501. Conclusion: There is no relationship between attitudes, the role of teachers, and the availability of facilities with CHLB and there is a relationship between family parenting and the role of parents with students' CHLB.